El papel de la víctima en la tramitación de los procesos por el delito de maltrato: Un análisis sobre su incidencia en la eficacia de la Ley 8589 - Pérez Matamoros, Sammy (2026)
This essay aims to address the amendments introduced by Law N° 8589 regarding the procedural treatment of the victim and its relationship with effectiveness in the prosecution of the crime of mistreatment as established therein.